1986
DOI: 10.7326/0003-4819-104-1-41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 9-(1,3-Dihydroxy-2-Propoxymethyl) Guanine on Serious Cytomegalovirus Disease in Eight Immunosuppressed Homosexual Men

Abstract: Eight immunosuppressed homosexual men with cytomegalovirus viremia--seven with serious bilateral retinitis, one with colitis in addition to retinitis, and one with pneumonitis only--were treated with a new acyclovir derivative, 9-(1,3-dihydroxy-2-propoxymethyl) guanine, which has excellent in-vitro activity against cytomegalovirus. All patients had virologic and clinical improvement, but substantial leukopenia developed in three patients. Both clinical relapses and viral relapses occurred frequently, usually w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Recently it has been shown that 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG) has potent activity against CMV in vitro (Smee et al, 1983;Mar et al, 1983;Tyms et al, 1984a) with low toxicity (Cheng et al, 1983;Tyms et al, 1984a). Most important, this drug was effective in treating CMV infection in vivo (Shepp et al, 1985;Felsenstein et al, 1985;Bach et al, 1985;Masur et al, 1986;Collaborative DHPG Treatment Study Group, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG) has potent activity against CMV in vitro (Smee et al, 1983;Mar et al, 1983;Tyms et al, 1984a) with low toxicity (Cheng et al, 1983;Tyms et al, 1984a). Most important, this drug was effective in treating CMV infection in vivo (Shepp et al, 1985;Felsenstein et al, 1985;Bach et al, 1985;Masur et al, 1986;Collaborative DHPG Treatment Study Group, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Although a similar antiviral effect has been observed in marrow transplant patients treated for CMV pneumonia, with both inhibition of virus excretion and a marked decrease in the titer of CMV recovered from lung tissue after treatment, survival from CMV pneumonia was not improved in initial trials (5,15,16). Moreover, ganciclovir treatment has been associated with transient marrow suppression in 25 to 50% of patients treated (3,6,7,9,12,15,16).…”
mentioning
confidence: 87%
“…Initial studies in marrow transplant patients and in patients with acquired immune deficiency syndrome (AIDS) indicate substantial antiviral activity in vivo as well. Clinical improvement has been observed among AIDS patients treated for CMV retinitis, enteritis, or pneumonia in uncontrolled studies (3,7,9,12). Although a similar antiviral effect has been observed in marrow transplant patients treated for CMV pneumonia, with both inhibition of virus excretion and a marked decrease in the titer of CMV recovered from lung tissue after treatment, survival from CMV pneumonia was not improved in initial trials (5,15,16).…”
mentioning
confidence: 93%
“…ACV has been used for the treatment of acute infectious mononucleosis and other EBV-associated disorders; however, the drug appears to be of little or no benefit (6). DHPG has also been used clinically and was found to have substantial bone marrow toxicity (18). Furthermore, the potential incorporation of these compounds into cellular DNA could present some problems.…”
Section: Epstein-barr Virus (Ebv) Is a Major Pathogen In Humansmentioning
confidence: 99%